2021
DOI: 10.1007/978-3-030-53637-4
|View full text |Cite
|
Sign up to set email alerts
|

Framing TTIP in the European Public Spheres

Abstract: Palgrave Studies in European Political Sociology addresses contemporary themes in the field of Political Sociology. Over recent years, attention has turned increasingly to processes of Europeanization and globalization and the social and political spaces that are opened by them. These processes comprise both institutional-constitutional change and new dynamics of social transnationalism. Europeanization and globalization are also about changing power relations as they affect people's lives, social networks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Negative approaches typical of Euroscepticism are avoided. The local news in this study does not so much follow the tendency towards dissent observed in recent years around Europe (Oleart 2021). However, the aforementioned thematic agenda of the media could also be indicative of a pessimistic approach towards the European project.…”
Section: Negativitycontrasting
confidence: 68%
“…Negative approaches typical of Euroscepticism are avoided. The local news in this study does not so much follow the tendency towards dissent observed in recent years around Europe (Oleart 2021). However, the aforementioned thematic agenda of the media could also be indicative of a pessimistic approach towards the European project.…”
Section: Negativitycontrasting
confidence: 68%
“…Type II politicisation, on the contrary, is characterised by debates focused on economic issues and overall positive towards FTAs, while also emphasising national and sectoral interests in their claims. As shown in Table 2, the findings suggest there is a divide between, on the one hand, two countries at the EU's core, France and Germany, which are more critical of the FTAs (type I), and other countries which are somewhat closer to the periphery, like Spain and Italy, where although the salience of TTIP and CETA was unprecedented (Oleart, 2021), the debate was still skewed in favour of the EU's trade policy (type II). These patterns, on the one hand, in part, confirm our more specific expectations (I) and (II); on the other hand, the findings are complicated by the fact that the first cluster also includes Poland and the second cluster, also comprises Denmark.…”
Section: Analysing T Ypes Of Politicisationmentioning
confidence: 99%
“…However, what is often missing-with some notable exceptions (Bauer, 2016;Oleart, 2021;Siles-Brügge & Strange, 2020)-is an effort to (i) unpick the overarching dividing lines of the debate on a politicised issue and (ii) examine the explanatory potential of diverging structural socio-economic trajectories in the EU, as predictors of the nature of those dividing lines, alongside policy-focused, actor-centred and other more conjunctural explanations. In this paper, while we cannot directly address how politicisation is shaping the EU as a global actor, our aim is to provide an empirical study which may help answering such questions, by highlighting cross-Member State patterns of politicisation.…”
Section: Understand Ing the Politicisation Of Eu Tr Ade Policymentioning
confidence: 99%
“…Thus, the EU has fragmented executive powers that are to be held accountable by multiple parliaments (see Crum & Fossum, 2009). This fragmentation is amplified by the absence of an integrated European public sphere (Koopmans & Statham, 2010; Oleart, 2021). As a consequence, the public visibility of whatever accountability takes place in the European Parliament is bound to remain low, certainly when compared to the visibility that national parliaments enjoy in national public spheres (Eisele, 2017).…”
Section: National Parliaments and The European Commission: A Case Of ...mentioning
confidence: 99%